008 OP: THE ENACTMENT OF COLLABORATION THROUGH MEETINGS: INSIGHTS FROM THE US-PEXa PROJECTb. (3rd March 2017) - Montgomery, CM; Chisholm, A; Parkin, S; Locock, L; ,
Abstract : How are the social relations of collaboration enacted? In this paper, we address this question by analysing a meeting of researchers at the University of Oxford and the Picker Institute, teams of frontline staff from six National Health Service (NHS) trusts, and a 'lay panel', brought together for the US-PEx project a . Drawing on the anthropology of organizational gatherings, we examine the enactment of social relations between these constituent groups through their participation in a 'learning community event'. The event took place over two days at the start of the project and was designed to build capacity for ward teams to take forward quality improvement work based on patient experience data by sharing learning and experiences, building inter- and intra-team relationships and establishing a network of support. The meeting was observed by a team of three ethnographers, with additional observations recorded by members of the research team and the 'lay panel'. Using these data, we describe the role of the meeting as, variously, a sense-making tool, a social validating mechanism, evidence of working on an issue, and a means of protest and resolution. Focusing not just on the meeting itself, but the before and after of the event, we examine how different participants generated, affirmed and contested the terms of collaboration. While the latter is assumed to exist independently of the meeting, we reflect here on the necessity of ongoing and future meetings to enact the social relations that define it. a US-PEx: Understanding how frontline staff use patient experience data for service improvement. b This abstract summarises independent research funded by the National Institute for Health Research (NIHR) under its Health Services and Delivery Research Programme (Grant Reference Number 14/156/06 ). The views expressed are those of the authors, and not necessarily those of the NHS, the NIHR or the Department of Health.